A COPD Primer - Panos, Ralph; Eschenbacher, William (De Gruyter, 2015)
In 2012 we received a grant from the Veterans Health Administration Office of Specialty Care entitled, (3z(BPatient-Centered Model for the Management of Chronic Obstructive Pulmonary Disease.(3y (BThe grant$1 (Bs goals were to enhance the recognition and diagnosis of COPD and implement a Patient-Centered Model for the Management of COPD. As the work on that proposal progressed, we realized that providers did not have an up-to-date, comprehensive, easily read, (3z(Bhow to(3y (Bmanual for the management of COPD despite all the advances in COPD care that have occurred over the past 5 years. Consensus documents such as the VA-DOD Guidelines were abbreviated summaries that were rarely used. From those discussions, the concept for this volume, a COPD Primer, developed. The goal was to develop a practical book that concisely presented COPD to providers with sufficient background and explanation of the physiologic and scientific rationale for various management strategies without becoming an esoteric academic work. We hope that this COPD Primer has achieved that goal and will be a useful, practical text for practitioners and medical trainees alike. The COPD Primer begins with an examination of what COPD is; it is really a syndrome, a constellation of historical features and clinical, physiologic, and radiographic findings. However, those elements come together in many different ways to create multiple different COPD phenotypes that are only now being recognized and used to define specific management strategies. COPD research has progressed beyond the simple classification of (3z(Bblue bloaters(3y (Band (3z(Bpink puffers.(3y (BNext, the epidemiology and economic consequences of COPD are reviewed. Bill Eschenbacher presents an approach to the patient with respiratory symptoms with detailed discussions of pulmonary function testing and how airflow limitation/obstruction is identified by spirometry and the use of lung imaging to identify individuals with COPD. Michael Borchers and Gregory Motz summarize current evidence implicating genetics, proteolytic imbalance, oxidative stress, inflammation, occupational and environmental exposures, and innate and adaptive immune function in the pathogenesis of COPD and the implication of these findings to future treatments. The single most important intervention in the prevention and treatment of COPD is smoking cessation. Shari Altum, Katherine Butler, and Rachel Juran present a practical approach to smoking cessation utilizing motivational interviewing in combination with pharmacologic interventions. Then, they expand upon these concepts to provide practitioners with convenient, realistic suggestions to encourage patient self-management in all aspects of COPD care and overall health. Ahsan Zafar reviews the natural history, recently described COPD phenotypes, and gender differences that clearly illustrate the broad spectrum of disease that comprises the term, COPD. The cover illustration highlights Dr. Zafar$1 (Bs creative and artistic talents. The extensive nonpulmonary aspects of COPD are reviewed by Ralph Panos in an examination of COPD$1 (Bs multi-organ manifestations. Next, the effect of COPD on sleep and the overlap syndrome, the concurrence of COPD and obstructive sleep apnea, and its consequences are presented. Jean Elwing examines the effect of COPD on the pulmonary vasculature with a detailed discussion of the evaluation and management of pulmonary hypertension associated with COPD. COPD$1 (Bs effects on psychosocial functioning and familial interactions are presented by Mary Panos and Ralph Panos. The focus of the Primer then shifts from manifestations to treatment with a discussion of stable COPD management. With the current plethora of devices for delivering respiratory medications, it is difficult for both patients and providers to sustain knowledge of their proper use. Aaron Mulhall presents a practical guide to correct inhaler use that reviews all the current devices. Folarin Sogbetun then reviews the management of outpatient COPD exacerbations and Nishant Gupta discusses the approach to the patient hospitalized with COPD. Because patients with COPD often see multiple subspecialty physicians in addition to their primary care providers, interdisciplinary communication and coordination of care is essential for their management; Sara Krzywkowski-Mohn reviews the interactions between primary and specialty care for the patient with COPD with suggestions for improved communication and care coordination. Finally, advance care planning including palliative care and hospice is reviewed with a discussion of how end stage COPD affects not only the patient but also their family and social network. This COPD Primer incorporates the knowledge that we have learned over the past several years during the development and implementation of a patient-centered model for the management of COPD. It was written with the explicit goal of assisting both the practicing provider and medical trainee in the care of patients with COPD.s
English
Keywords: Internal Medicine